Genetic instability-related lncRNAs predict prognosis and influence the immune microenvironment in breast cancer - Lv, Zhenyi; Wang, Qiang; Liu, Xuxu; Du, Zhiwei; Liang, Wenping; Liu, Tianming; Zheng, Yi; Ma, Biao; Xue, Dongbo (Frontiers in Genetics, 2022)
Genome instability is a hallmark of cancer, and the function of lncRNAs in regulating genomic stability has been gradually characterized. However, the role of lncRNAs associated with genome instability is still unclear in breast cancer. Here we constructed a genomic instability-related lncRNA model including U62317.4, SEMA3B-AS1, MAPT-AS1, AC115837.2, LINC01269, AL645608.7, and GACAT2. The patients could be divided into high- and low-risk groups through this model, and patients in the high-risk group have a worse prognosis. Furthermore, the differentially expressed genes between the high- and low-risk groups were enriched in immunity and cornified envelope formation pathways. More important, M2 macrophages were increased in the immune microenvironment of the high-risk group. In summary, the seven lncRNAs related to genome instability may influence the development of breast cancer through immune infiltration and keratinization. It provided a wider insight into breast cancer development and treatment.